Evolution of waste and circular economy: pre-and post‑Covid‑19 - Jamaludin, Husna (Springer Nature, 2025)
Waste generation is a serious problem in both developed and developing countries, exacerbated by Covid-19. In recent years, circular economy is a promising solution to sustainable waste management. Therefore, this study aims to present the evolution of waste and circular economy research before, during and after Covid-19. A bibliometric analysis of 1,149 scientific articles from the Scopus database in July 2023 was conducted, using Microsoft Excel, Vosviewer and biblioshiny. The results were obtained using standard bibliometric indicators such as publication and citation trends, influential countries, institutions, authors and sources, and keyword analysis. The results show that the number of publications and citations in this field has increased tremendously over the years, indicating the importance of knowledge for both developed and developing countries. The main actors in this field are both developed (European) and developing countries/institutions. Many sources of the publications are from reputable journals. Keyword analysis shows that waste management is the main topic before and after Covid-19, with plastic and agricultural waste being more prominent after Covid-19. The findings provide some direction for future research and underline the importance of using appropriate tools to undertake a thorough bibliometric study.